Inside Back Cover: Gravure‐Printed ZnO in Fully Roll‐to‐Roll Printed Inverted Organic Solar Cells: Optimization of Adhesion and Performance (Energy Technol. 4/2015). Issue 4 (April 2015) - Vilkman, Marja; Apilo, Pälvi; Välimäki, Marja; Ylikunnari, Mari; Bernardi, Andrea; Po, Riccardo; Corso, Gianni; Hast, Jukka
Abstract : Keep it rolling! The cover image shows a portion of a solar cell roll on a 30 cm wide plastic substrate, patterned by gravure and rotary screen printing processes. The cells consist of an inverted structure, where the gravure‐printed zinc oxide layer was exposed to a roll‐to‐roll plasma treatment to increase the adhesion and performance of the cells. The Full Paper by Marja Vilkman and colleagues at VTT Technical Research Centre of Finland and ENI S.p.A. onpage 407 shows that the process can reach average solar cell performance of 2.9 % by using commercially available materials.